2022
DOI: 10.1371/journal.pone.0262827
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, attitude, and practice related to the COVID-19 pandemic among undergraduate medical students in Indonesia: A nationwide cross-sectional study

Abstract: Introduction The potential role of medical students in raising awareness during public health emergencies has been acknowledged. To further explore their potentials as public educators and role models for the communities during the coronavirus disease 2019 (COVID-19) pandemic, this study aims to assess the knowledge, attitude, and practice of these students toward COVID-19. Methods An online cross-sectional survey was conducted among undergraduate medical students in Indonesia. Socio-demographics characteris… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
15
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(41 citation statements)
references
References 22 publications
11
15
2
1
Order By: Relevance
“…The ORs indicated that male sex and age were predictors of high total KAP, and education level was negatively associated with high total KAP. Women scored higher than men for COVID-19-related knowledge, which was consistent with past studies ( 17 , 26 , 32 ). Highly educated respondents with a master's degree or above had better knowledge levels than respondents with lower education levels.…”
Section: Discussionsupporting
confidence: 92%
“…The ORs indicated that male sex and age were predictors of high total KAP, and education level was negatively associated with high total KAP. Women scored higher than men for COVID-19-related knowledge, which was consistent with past studies ( 17 , 26 , 32 ). Highly educated respondents with a master's degree or above had better knowledge levels than respondents with lower education levels.…”
Section: Discussionsupporting
confidence: 92%
“…The current study highlighted the poor practices of students regarding COVID-19, similar to findings reported in studies conducted among university students (13,69,70,72). For instance, a study in Indonesia reported an overall practice of 51.5% among university students (69), in line with findings from Ethiopia (70). Most participants reported wearing facemasks in public, which corroborate findings from other studies (69,73).…”
Section: Discussionsupporting
confidence: 90%
“…In particular, males and those with a lower education level have less understanding of COVID-19, making them especially vulnerable to the outbreak. Prior studies into the correlation between sociodemographic characteristics and knowledge level during the COVID-19 outbreak in China produced similar results [57,70], to Hong Kong [71], Pakistan [72] Malaysia [74] and Indonesia [75]. These studies in different countries revealed that the results differed among nations and were impacted by the types of human settlements.…”
Section: Discussionmentioning
confidence: 68%